Rancang Bangun Pengendali Air Condisioner (Ac)Gedung Bank Central Asia Kcu Diponegoro Surabaya Berbasis Arduin - Bagus Nurdila Eko Kuncoro; Anang Widiantoro (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2018)
The use of Air Conditioner (AC) in an important position and becomes the main thing. BCA diponegoro has a total of 28 AC conditioners which are manually and need an engine for AC conditioning. This research looks to build A prototype control system that can control AC electricity automatically, centralized and computerized. So that it can help engineers monitor, control and control building AC conditioners effectively and efficiently. The design of the system using the Micro-controller AT MEGA 2560 as a controlling tool in controlling the electricity AC of the BCA KCU Diponegoro building. And use Visual Basic. NET 2010 as an HMI (Human Machine Interface). The results of this tool are able to control AC electricity in the Diponegoro KCU BCA building automatically, centrally and can be controlled by a Personal Computer.